Efisiensi pakan bertepung kijing Taiwan (Anodonta woodiana) bagi pertumbuhan ikan mas (Cyprinus caprio L.) - Mangkapa, Arliani; Lumenta, Cyska; Mokolensang, Jeffrie F. (Universitas Sam Ratulangi, 2017)
The objectives of research were to determine the effect of different composition of Taiwanese mussel powder-supplemented feed on absolute growth, daily growth, relative growth, feed efficiency and food conversion ratio for carp fingerling; and to determine the best composition of Taiwanese mussel powder-supplemented feed that gave the best response on carp fingerling. The research was conducted at Laboratory of Aquaculture Technology by means of 15 aquaria with a density of 10 fishes (3-5 cm in length) per aquarium. The research implemented Complete Randomized Design with five treatments, each with three replications. The treatments included A= 0, B= 10, C= 20, D= 30, and E= 40% Taiwanese mussel carcass powder. The fish were fed three times a day at 6% of body weight. Research result showed the best absolute, daily, and relative growth, feed efficiency and food conversion ratio was observed at treatment E. It was concluded that feed supplemented with 40% of Taiwanese mussel carcass powder demonstrated the best response on and growth, feed efficiency and food conversion ratio.Keywords: Taiwanese mussel powder, growth, feed efficiency, feed conversion ratio